Chondroblastic osteosarcoma of the mandible: case report - Loara Gabriela R. Oliveira; John Lennon S. Cunha; Bruno T. Bezerra; Maria de Fátima B. Melo; Juliana B. M. Fonte; Ricardo Luiz C. Albuquerque Jr (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT We report the case of a 32-year-old male patient, who was subjected to cone-beam tomography for planning the removal of an unerupted tooth. Cone-beam CT scans revealed the presence of a mixed lesion with poorly defined limits in the left posterior mandibular region, with "sun-ray" periosteal reaction. An incisional biopsy was performed and the diagnosis was chondroblastic osteosarcoma. In this paper, a discussion of the differential diagnosis criteria and treatment of this unusual malignant neoplasm is performed. Thus, it is intended to provide information that will help in the study of management protocols for the increasingly effective treatment of gnathic osteosarcomas.